PENGARUH KOORDINASI CAMAT TERHADAP KEBERHASILAN PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN ESSANG SELATAN KABUPATEN KEPULAUAN TALAUD - PUSIDA, MAWARJATI; LENGKONG, FLORENCE DAICY; LALOMA, ALDEN (Sam Ratulangi University, 2019)
The aim of the research was to determine the influence of the sub-district head coordination onthe success of the community empowerment program in Essang District, Talaud Islands Regency. This studyuses quantitative methods. The sub-district head coordination variables are observed from indicators ofcommunication, cooperation, synchronization, and integrity or unity of action; while the success variableof the community empowerment program is measured from indicators of welfare, access, critical awareness,participation and control. The research respondents were 40 people from the sub-district government,village government, BPD, LPM and the community. Instruments and data collection techniques usingquestionnaires and assisted with quide interviews. The analysis technique for hypothesis testing usedstatistical regression of the product moment linear regression. The results of data analysis showedregression coefficients and the sub-district head coordination variable correlation coefficient for the successof community empowerment programs in the sub-district South Essang is positive and significant, so it wasconcluded that the sub-district head coordination had a positive and significant correlation with the successof the community empowerment program in Essang District. Based on the results of this study, it can berecommended that sub-district head coordination in community empowerment programs needs to beimproved both in program planning and implementation by streamlining the sub-district level coordinationforum, conducting direct monitoring of the implementation of community empowerment programs/activitiesin the sub-district area, and evaluating community empowerment programs/activities in the sub-district.Keywords: Coordination, Sub-district Head, Community Empowerment.